2009
DOI: 10.1063/1.3173609
|View full text |Cite
|
Sign up to set email alerts
|

Do fluorescence and transient absorption probe the same intramolecular charge transfer state of 4-(dimethylamino)benzonitrile?

Abstract: International audienceWe present here the results of time-resolved absorption and emission experiments for 4-(dimethylamino)benzonitrile in solution, which suggest that the fluorescent intramolecular charge transfer (ICT) state may differ from the twisted ICT (TICT) state observed in transient absorption

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 21 publications
10
71
0
Order By: Relevance
“…6,7,12 The TICT state absorption at 330 nm decays in ∼ 4.8 ns, which is significantly longer than the decay time (2.9 ns) of the ICT fluorescence at 490 nm. 7 The rise time of the ICT fluorescence, ∼ 3.1 ps (which is the same as the fast-component decay time of the LE fluorescence), also differs from that (∼ 4.3 ps) of the TICT-state transient absorption (TA) at 420 nm.…”
Section: Frommentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,12 The TICT state absorption at 330 nm decays in ∼ 4.8 ns, which is significantly longer than the decay time (2.9 ns) of the ICT fluorescence at 490 nm. 7 The rise time of the ICT fluorescence, ∼ 3.1 ps (which is the same as the fast-component decay time of the LE fluorescence), also differs from that (∼ 4.3 ps) of the TICT-state transient absorption (TA) at 420 nm.…”
Section: Frommentioning
confidence: 99%
“…6,7,12 The TICT state absorption at 330 nm decays in ∼ 4.8 ns, which is significantly longer than the decay time (2.9 ns) of the ICT fluorescence at 490 nm. 7 The rise time of the ICT fluorescence, ∼ 3.1 ps (which is the same as the fast-component decay time of the LE fluorescence), also differs from that (∼ 4.3 ps) of the TICT-state transient absorption (TA) at 420 nm. 7 The disparity between the rise and decay times of the ICT fluorescence and those of the TICT-state TA suggest that the fluorescence ICT state differs from the TICT state observed in transient absorption.…”
Section: Frommentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of DMABN and some related molecules, the evidence of the participation of ps* states in the relaxation processes leading to the population of ICT states rests upon recent experimental studies carried out by Lim, Gustavsson and co-workers. 24 The results obtained by these authors using time resolved transient absorption and fluorescence up-conversion experiments point out to the existence of two different relaxation pathways for the initial excited population of DMABN. Specifically, the decay time of the LE state was found to be similar to the rise time of the TICT transient absorption, and different from the ICT fluorescence feature measured by fluorescence up-conversion techniques, pointing towards the existence of more than one ICT state present in the molecule on polar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, however, it has been suggested that a low-lying ps* state arising from the promotion of an electron from the aromatic p to a s*-like orbital localised on the cyano (CRN) group in DMABN could be a major precursor of the ICT state. [21][22][23][24][25][26][27] This idea is based on and influenced by previous ab initio computational studies where a minimum in the ps* ICT state was located. 5,28,29 The involvement of ps* states in different photoinduced processes has been increasingly recognised over the last few years and it is nowadays accepted that this kind of excited state plays an important role in processes ranging from molecular photodissociation to ICT formation.…”
Section: Introductionmentioning
confidence: 99%